Energy-efficient traction electric drive for contact-battery shunting electric locomotive - Chernyshenko, Ievhen (National Technical University "Kharkiv Polytechnic Institute", 2024)
It is analyzed the use of shunting electric locomotives on railways. This type of rolling stock is becoming widely used, as it reduces the cost of transportation and harmful environmental impact.
Keywords: traction electric drives; energy efficiency; rolling stock; electric locomotives